Let ( x 1 , y 1 , z 1 ) , ( x 2 , y 2 , z 2 ) , … , ( x n , y n , z n ) be the rational solutions to the following system of equations
x + y + z = 0 x 3 + y 3 + z 3 = 1 8 x 7 + y 7 + z 7 = 2 0 5 8
Evaluate:
i = 1 ∑ n x i y i z i
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Amazing solution! :D
Log in to reply
@Sean Ty i did the whole thing and could not understand the exact ask of the question...ended up typing 6,18, and 3 and lost my chance.. God why ? ;__; By the way..this appeared in Gazeta Mathematica :D
You can definitely approach the problem using Newton's Sums (read the solution by @Alan Enrique Ontiveros Salazar) but we will approach the following problem in a different way by setting up some recurrence relations (although it's a bit long)
So, let S n = x n + y n + z n
We already know the following values of S n -
S 0 = x 0 + y 0 + z 0 = 3
S 1 = x + y + z = 0
S 3 = x 3 + y 3 + z 3 = 1 8
S 7 = x 7 + y 7 + z 7 = 2 0 5 8
Now, we would try to find out the values of x y z and x y + y z + z x . (You'll see further that why are we doing so)
Since x + y + z = 0
3 x y z = x 3 + y 3 + z 3 ⇒ x y z = 1 8 / 3 = 6
Now, we just need to show that ( x , y , z ) are rational. So,
x y + y x + z x = 2 ( x + y + z ) 2 − ( x 2 + y 2 + z 2 ) = − 2 S 2
Now, we would set up the recurrence relation for S n . We do so by writing up the characteristic equation for S , which is -
( S − x ) ( S − y ) ( S − z ) = 0 ⇒ S 3 − ( x + y + z ) S 2 + ( x y + y z + z x ) S − x y z = 0 ⇒ S 3 − 2 S 2 S − 6 = 0
[You can read about the recurrence relations here - http://www.webpages.uidaho.edu/~markn/395/pdf/rec-eq.pdf
And for more practice on recurrence equations, you may try out these problems by @Aditya Raut- https://brilliant.org/profile/aditya-5j3pzo/sets/bashing-unavailable-awesome-problems/]
Therefore, the recurrence relation that we generate from the above equation is -
S n + 3 = 2 S 2 S n + 1 + 6 S n
Therefore, we get -
S 5 = 2 S 2 S 3 + 6 S 2 = 9 S 2 + 6 S 2 = 1 5 S 2
S 7 = 2 S 2 S 5 + 6 S 4 = 2 1 5 S 2 2 + 6 ( 2 S 2 2 + 6 S 1 ) = 2 2 1 S 2 2
Now observe that, 2 S 2 3 S 3 = 5 S 5
Similarly, we can also see that, 2 S 2 5 S 5 = 7 S 7
[You may be interested in solving this generalized version of the problem in USAMO 1982, Problem 2 - http://www.artofproblemsolving.com/Wiki/index.php/1982 USAMO Problems/Problem_2]
Therefore, after plugging in values of S 3 and S 5 , we get - S 2 = x 2 + y 2 + z 2 = 1 4
This yields, x y + y z + z x = − 7
Now, let x , y , z be the roots of a cubic equation. This yields - t 3 − ( x + y + z ) t 2 + ( x y + y z + z x ) t − x y z = t 3 − 7 t − 6 = ( t + 1 ) ( t + 2 ) ( t − 3 )
Hence, we find the rational solutions for ( x , y , z ) = ( − 1 , − 2 , 3 )
Therefore, ∑ i = 1 n x i y i z i is equal to the all the permutations of ( x , y , z ) which yields ∑ i = 1 n x i y i z i = 6 + 6 + 6 + 6 + 6 + 6 = 3 6
I know you can approach it with Newton's Sums. The title was supposed to be intimidating (kind of) :T
Log in to reply
I intentionally, presented a solution using simple recurrence relations, just to share another method of solving the problem.
Problem Loading...
Note Loading...
Set Loading...
Let P ( x ) = m 3 + b m 2 + c m + d with roots x , y and z ; and let S k = x k + y k + z k . We are given S 1 = 0 , S 3 = 1 8 and S 7 = 2 0 5 8 . Now, by Newton's Sums we have:
S 1 = 0 = − b ⟹ b = 0
S 2 = − b S 1 − 2 c ⟹ S 2 = − 2 c ⟹ c = − 2 S 2
S 3 = 1 8 = − b S 2 − c S 1 − 3 d ⟹ d = − 6
By Vieta's formulas, we know that x y z = − d , hence x y z = 6 . This value is rational, but there are six possible permutations of the triple ( x , y , z ) , hence the asked value is 6 x y z = 3 6 .
To prove that the triple (x,y,z) is rational we can obtain S 7 by recursion:
S 7 = 4 2 c 2 ⟹ 2 0 5 8 = 4 2 c 2 ⟹ c = ± 7 .
So, there are two possible polynomials for P ( m ) = m 3 ± 7 m − 6 . m 3 − 7 m − 6 factors as ( m + 1 ) ( m + 2 ) ( m − 3 ) showing that ( x , y , z ) = ( − 1 , − 2 , 3 ) and all its permutations are rational.